Proses Difusi Untuk Meningkatkan Kualitas Deteksi Tepi Citra - Pramana, Danar Ardian (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2024)
Image processing is generally used to repair an image that is affected by interference or noise. The goal is so that the resulting image is easy for humans to understand. Edge detection is one of the scientific fields of image processing. To get better image detection results, a diffusion process can be used using the two-dimensional diffusion equation. Initial conditions and boundary conditions are needed in the two-dimensional diffusion equation which is then used to improve image edge detection. The scheme used is an explicit scheme. The time variable is important in this process. The edges of the image will change increasingly as increases. This process continues until . Several examples will be given to illustrate the results for the diffusion process in image edge detection.